Pediatric collaborative care outcomes in a regional model - Parkhurst, John T.; Garcia-Goetting, Catherine; Peist, Eric; Ballard, Rachel; Romba, Courtney; Lavigne, John V. (Frontiers in Psychiatry, 2023)
Background: Despite a movement toward hospital-based medical centers acquiring pediatric primary care offices, many primary care pediatricians still work in small, independent practices. To expand mental health care access, service delivery models must consider primary care practice needs and regionally-available resources. Objective: This report describes the implementation and evaluation of the Mood, Anxiety, ADHD Collaborative Care (MAACC) program over a four-year period. MAACC. MAACC engaged 97 pediatric primary care clinicians across 39 practices in mental health training and supported the treatment of referred patients through a collaborative care model. To support psychosocial treatment needs we built a child community therapy referral network of 213 licensed psychotherapy providers. Methods: Data were collected on service delivery patterns (e.g., referrals, treatment use, attrition) and patient outcomes. Measures included parent and youth PROMIS anxiety and depression short forms and the Parent NICHQ Vanderbilt. Results: 696 youth aged 6-18 were evaluated and provided treatment recommendations. Anxiety disorders were the most common diagnosis (45.4%), followed by ADHD (30.7%) and mood disorder (17%). For youth with an anxiety or mood disorder, significant improvement was observed from baseline to any initial follow-up and from baseline to 6-, 12-, and 18- weeks on youth and parent measures of anxiety and depression. For youth with ADHD, significant improvement was observed from baseline to any initial follow-up measure and at 6- and 18-weeks on parent reported inattentive symptoms. Significant differences in treatment outcomes were identified for youth with anxiety receiving psychotherapy alone and medication management and psychotherapy. Conclusions: MAACC utilization and patient outcomes suggest that real-world collaborative care can effectively provide high quality care while cultivating increased primary care treatment capacity and building on existing community resources.